2016
DOI: 10.1308/rcsann.2016.0239
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating foreign body in the masticator space with injury to the internal maxillary artery: a surgical challenge

Abstract: INTRODUCTION Foreign bodies (FBs) in the masticator space (MS) are a unique problem because of the difficulty of accessing this deep compartment within the head and neck. In addition, MS contents include critical structures such as the internal maxillary artery (IMA) and mandibular nerve. CASE HISTORY A 39-year-old tradesman was involved in a construction accident whereby a metallic projectile from a machinery drill penetrated his left cheek. Computed tomography revealed a metallic object of dimension 1.9 Â1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Infratemporal fossa contains internal maxillary artery, pterygoid venous plexus of veins. Wulkan et al [3] reported complications associated with extraction of such foreign bodies due to internal maxillary artery injury, which can be surgically uncontrollable and potentially fatal [4]. Some delayed complications have also been reported like aneurysm [5] and erosion of the vessel wall [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infratemporal fossa contains internal maxillary artery, pterygoid venous plexus of veins. Wulkan et al [3] reported complications associated with extraction of such foreign bodies due to internal maxillary artery injury, which can be surgically uncontrollable and potentially fatal [4]. Some delayed complications have also been reported like aneurysm [5] and erosion of the vessel wall [6].…”
Section: Discussionmentioning
confidence: 99%
“…But these approaches are rarely required for foreign bodies. In the past infratemporal fossa foreign bodies have been explored using pre auricular approach [7], intraoral approach [8], endoscopic intraoral approach [4], transmaxillary endoscopic approach [9] We explored the foreign body using infraorbital horizontal incision. As the periorbita was being raised from the orbital floor foreign body was palpated and confirmed using 0-degree endoscope and was pulled out under vision without any post operative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Infratemporal fossa contains internal maxillary artery, pterygoid venous plexus of veins. Wulkan et al [3] reported complications associated with extraction of such foreign bodies due to internal maxillary artery injury, which can be surgically uncontrollable and potentially fatal [4]. Some delayed complications have also been reported like aneurysm [5] and erosion of the vessel wall [6].…”
Section: Discussionmentioning
confidence: 99%